Motivation factors Affecting Virtual Goods Purchase Intention in Online Games of Generation Z Consumer: แรงจูงใจที่ส่งผลต่อความตั้งใจซื้อสินค้าเสมือนในเกมออนไลน์ของผู้บริโภคเจเนอเรชันซี - Pitiphat, Supagrit (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ การใช้จ่ายเงินจริงกับสินค้าเสมือนกลายเป็นพฤติกรรมผู้บริโภครูปแบบหนึ่งที่ได้รับความนิยม โดยเฉพาะในกลุ่มเจเนอเรชันซี กรอบแนวคิดการวิจัยนี้สร้างขึ้นจากทฤษฎีการใช้ประโยชน์และความพึงพอใจ (Uses and Gratifications Theory: U & G Theory) เพื่อตรวจสอบบทบาทของแรงจูงใจด้านการใช้งาน ด้านสังคม และด้านความเพลิดเพลิน ที่ส่งผลต่อความตั้งใจซื้อสินค้าเสมือนในเกมออนไลน์ โมเดลการวิจัยได้รับการทดสอบด้วยข้อมูลที่เก็บรวบรวมจากกลุ่มตัวอย่างที่มีประสบการณ์ซื้อสินค้าเสมือนภายในเกมออนไลน์ในจังหวัดอุดรธานี จำนวน 400 ราย ด้วยวิธีการสุ่มแบบหลายขั้นตอน วิเคราะห์ข้อมูลด้วยสถิติเชิงพรรณนา และการวิเคราะห์โมเดลสมการเชิงโครงสร้าง จากการศึกษา พบว่า โมเดลมีความสอดคล้องกับข้อมูลเชิงประจักษ์ โดยความตั้งใจซื้อสินค้าเสมือน ได้รับอิทธิพลทางตรงเชิงบวกจากแรงจูงใจด้านการใช้งาน แรงจูงใจด้านสังคม และแรงจูงใจด้านความเพลิดเพลิน สำหรับผู้เผยแพร่และให้บริการเกมออนไลน์ สามารถใช้ผลการวิจัยนี้ในการออกแบบสินค้าเสมือน ABSTRACT Spending real money on virtual goods has become a popular form of consumer behavior, particularly among generation Z (Gen Z). This conceptual framework builds on the unified Theory of Uses and Gratifications (U & G Theory) to examine the role of functional motivation, social motivation and hedonic motivation affecting intent to purchase virtual goods in online games. The research model is tested with data from 400 consumers with the experience of purchasing virtual goods in online games, Udon Thani province. By using multi-stage sampling methods. The statistics employed in the research were descriptive statistics and structural equation model. The results showed that the conceptual model aligned with the empirical data. The findings of this research indicated that virtual goods purchase intention are direct positive influenced by functional motivation, social motivation and hedonic motivation. For online game publisher, this research results should be used to design a virtual goods.